(untitled) (Nordic Journal of African Studies, 2005)
Cultism has become a major social problem both within and outside the Nigerian universities. The origin of cultism in the Nigerian universities can be traced to the Pyrates Confraternity that was founded by the Nobel Laurete, Wole Soyinka and others at the University College, Ibadan (now called the University of Ibadan), in 1953. The confraternity which was non-violent and whose activities were never shrouded in secrecy resembled the sororities and fraternities found in many American university campuses. The aims of the Pyrates confraternity were lofty and noble. They wanted an end to tribalism; colonial mentality and they wanted to revive the age of chivalry. Unfortunately towards the end of 1960’s, the original aims of the Pyrates Confraternity were abandoned. The confraternity gradually metamorphosed into a secret cult that was later to proliferate into many splinter groups. This change was accelerated by yet other changes taking place both at the universities and the entire Nigerian society. The changes observable in the Nigerian society included violent military coups, state, sponsored political assassinations proliferation of ethnic militia, communal clashes and total erosion of the traditional family values. Changes occurring within the universities included overcrowdness, under funding, deteriorated infrastructure and lack of virile students union activities. The emergency of secret cultism has been characterized by some bizarre and violent activities which include, physical torture as a means of initiating new members, maiming and killing of rival cult members and elimination of real and perceived enemies. To effectively combat secret cultism, the universities must enjoy improved funding, recreational academic facilities must be improved and virile students union activities must be encouraged. For the general Nigerian society, the present culture of violence in the society must be curtailed.